CHRONIC ALLOGENEIC DISEASE : III. GENETIC REQUIREMENTS FOR THE INDUCTION OF GLOMERULONEPHRITIS - Gleichmann, Helga (The Rockefeller University Press, 1972)
The pathogenesis of glomerulonephritis in F(1) hybrid mice injected with parental spleen cells was investigated in several ways. Whenever glomerulonephritis developed, the lesion had the typical morphology produced by antigen-antibody complexes. Experiments employing backcross mice demonstrated that the antigen is supplied by the recipient and that it is specified by the H-2 gene complex, or by a locus closely linked to H-2. The source of the antibody was investigated by staining glomerular lesions with fluorescein isothiocyanate-tagged anti-immunoglobulin allotype sera. Only donor-type allotypes could be detected. The ability of the donor's immunocytes to respond to the recipient's histocompatibility antigens in such a way as to produce nephritogenic immune complexes varied from strain to strain, and seemed to be controlled by a gene unrelated to H-2. The results suggest that cell surface antigens, such as histocompatibility antigens, may be of importance in the pathogenesis of several kinds of glomerulonephritis.